UPAYA GURU DALAM MENGATASI KESULITAN MEMBACA, MENULIS, DAN MENGHITUNG (STUDI KASUS PADA SDN KUTA PASIE KABUPATEN ACEH BESAR) - Silvia Sandi Lubis; Al Juhra; Nur Helmi (Prodi PGMI FTK UIN Ar-Raniry Banda Aceh bekerjasama dengan PW PERGUNU Aceh, 2022)
Teachers are the most important component in the world of education and occupy a respectable place in society. Teachers have a very big influence on changes in the behavior of their students. Reading, writing and calculating are skills that must be owned and mastered globally. Based on the results of observations made at SDN Kuta Pasie, information was obtained that there were students who had difficulty reading, writing and calculating. The purpose of this study was to analyze the efforts made by the teacher in overcoming reading, writing and arithmetic difficulties, and to analyze the obstacles faced in efforts to deal with reading, writing and numeracy difficulties at SDN Kuta Pasie. This study uses descriptive qualitative research methods with data collection techniques of interviews, observation and documentation. The results of this study indicate that (1) Efforts made by teachers in overcoming difficulties in reading, writing and arithmetic are all educators who are graduates, learning programs according to the applicable curriculum, conducting initial tests for new students, conducting class workshops, carrying out activities Ramadan reading at the beginning of the fasting month, learning to read using the phonics method, collaborating with parents of students, and providing motivation to learn and encouragement to study enthusiasm for students. (2) The obstacles experienced by teachers are the lack of support and cooperation from parents of students, students who have difficulty reading, writing and calculating tend to be lazy to study, low student memory, unstable student psychology, and limitations of schools in providing supportive media in the process of learning to read, write and count.